A Comparative Study of Developmental Differences in Soil Rill Network Runoff and Slope Sediment Production Process. Issue 5 (February 2019) - Zhao, Xinkai; Gong, Jiaguo; Ren, Zheng; Wang, Danyang; Zhao, Yong; Yang, Miao; Shi, Bin
Abstract: To explore cultivated loessial soil and dark loessial soil rill network development and differences in slope runoff and sediment process. the three-dimensional laser scanning technology was used, the cultivated loessial soil and the dark loessial soil were taken as the research object, and the rain intensity of 60 mm / h and 90 mm / h was selected, and the simulated rainfall test of the 20 ° slope was carried out for 1 h. The results showed that the clay content of dark loessial soil was 2.5 times that of cultivated loessial soil. At the beginning of rainfall, the infiltration of black soil was slow, the runoff was earlier, and the runoff of slope was larger than that of loess. The landfall occurred earlier and the slope erosion was larger. but the cultivated loess soil is loose, poor in corrosion resistance and easy to be compacted by raindrops. In the second rainfall, the runoff on the loess slope was 1.4 times higher than that on the dark loess soil, and the erosion on the slope was higher than that on the dark loess soil. From the point of view of the development of rill net, the characteristic index of rill net of dark yellowed soil is larger than that of topsoil loess at the beginning of rainfall, but under the condition of rainfall in the middle and late period, the characteristic index of rill net of tilling layer loess is higher than that of dark loess. The rill development of cultivated yellow soil has the characteristics of late generation and fast development.